2020
DOI: 10.3390/toxins12110715
|View full text |Cite
|
Sign up to set email alerts
|

Association between Uremic Toxin Concentrations and Bone Mineral Density after Kidney Transplantation

Abstract: Although uremic osteoporosis is a component of mineral and bone disorder in chronic kidney disease, uremic toxin (UT) concentrations in patients with end-stage kidney disease and bone mineral density (BMD) changes after kidney transplantation have not previously been described. We hypothesized that elevated UT concentrations at the time of transplantation could have a negative impact on bone during the early post-transplantation period. Hence, we sought to determine whether concentrations of UTs (trimethylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…As for the other variables, we can observe the large difference in prevalence estimates between the transplanted population and the general population for hypercalcemia [ 54 ], hyperparathyroidism [ 55 ], hyperuricemia [ 55 ], hypervitaminosis D [ 56 ], sarcopenia [ 57 ], low muscle mass [ 58 ], fractures [ 59 ] and gout [ 55 ], indicating an increase in the prevalence of these metabolic disturbances and musculoskeletal disorders after kidney transplantation. In the case of osteopenia and osteoporosis, the difference in prevalence between the two populations is small, although it is true that in the studies [ 60 , 61 ] we have found in the general population, it is not divided into zones, as it is in the studies [ 13 , 15 , 19 21 , 24 , 25 , 29 , 35 – 37 , 39 , 43 ] in the transplanted population, which divide the prevalence into lumbar and femoral areas, so that no conclusions could be drawn when comparing the two populations with regard to these two variables analysed.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…As for the other variables, we can observe the large difference in prevalence estimates between the transplanted population and the general population for hypercalcemia [ 54 ], hyperparathyroidism [ 55 ], hyperuricemia [ 55 ], hypervitaminosis D [ 56 ], sarcopenia [ 57 ], low muscle mass [ 58 ], fractures [ 59 ] and gout [ 55 ], indicating an increase in the prevalence of these metabolic disturbances and musculoskeletal disorders after kidney transplantation. In the case of osteopenia and osteoporosis, the difference in prevalence between the two populations is small, although it is true that in the studies [ 60 , 61 ] we have found in the general population, it is not divided into zones, as it is in the studies [ 13 , 15 , 19 21 , 24 , 25 , 29 , 35 – 37 , 39 , 43 ] in the transplanted population, which divide the prevalence into lumbar and femoral areas, so that no conclusions could be drawn when comparing the two populations with regard to these two variables analysed.…”
Section: Discussionmentioning
confidence: 79%
“…The characteristics of the studies selected for this systematic review and meta-analysis are detailed in Table 1 . The study design was cross-sectional in 27 studies [ 11 , 12 , 14 , 15 , 18 21 , 23 32 , 34 – 37 , 41 45 ] (71.1%) and longitudinal in 11 [ 13 , 16 , 17 , 22 , 33 , 38 40 , 46 48 ] (28.9%). All these articles were published between 2001 and 2021, and most of them were conducted in Europe [ 13 , 14 , 16 , 19 24 , 29 – 31 , 35 , 36 , 38 , 39 , 42 ] (44.7%), although there were also studies from Asia [ 11 , 18 , 25 27 , 34 , 37 , 40 , 43 , 45 , 46 , 48 ] (31.6%), America [ 15 , 17 , 28 , 32 , 33 , 44 , 47 ] (18.4%) and Oceania [ 12 , 41 ] (5.3%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanisms and the cause-effect relationships between IxS and gastric cancer development remain to be further proven. Batteux et al [ 94 ] characterized osteoporosis as measured by bone mineral density (BMD) and by bone fractures after transplantation [ 94 ] ( Table 2 ). It was evident that serum IxS concentrations at the time of transplantation exhibited a positive relationship with BMD in the femoral neck and the total hip at one-month post-transplant [ 94 ], but p CS did not generate significant correlations.…”
Section: Resultsmentioning
confidence: 99%